Protective effect of SARS‐CoV‐2 preventive measures against ESKAPE and Escherichia coli infections - Gaspari, Rita; Spinazzola, Giorgia; Teofili, Luciana; Avolio, Alfonso W.; Fiori, Barbara; Maresca, Gian M; Spanu, Teresa; Nicolotti, Nicola; De Pascale, Gennaro; Antonelli, Massimo (European journal of clinical investigation, 2021)
Background/Objectives We investigated whether behavioral precautions adopted during Coronavirus disease (COVID‐19) pandemic also influenced the spreading and multidrug resistance (MDR) of ESKAPEEc (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii [AB], Pseudomonas aeruginosa, Enterobacter spp and Escherichia Coli, [EC]) among Intensive Care Unit (ICU) patients. Subjects/Methods We performed a single‐center retrospective study in adult patients admitted to our COVID‐19‐free surgical ICU. Only patients staying in ICU for more than 48 hours were included. The ESKAPEEc infections recorded during the COVID‐19 period (June 1, 2020 ‐ February 28, 2021) and in the corresponding pre‐pandemic period (June 1, 2019 ‐ February 28, 2020) were compared. An interrupted time series analysis was performed to rule out possible confounders. Results Overall, 173 patients in the COVID‐19 period and 132 in the pre‐COVID‐19 period were investigated. The ESKAPEEc infections were documented in 23 (13.3%) and 35 (26.5%) patients in the pandemic and the pre‐pandemic periods, respectively (p = 0.005). Demographics, diagnosis, comorbidities, type of surgery, Simplified Acute Physiology Score II, length of mechanical ventilation, hospital and ICU length of stay, ICU death rate, and 28‐day hospital mortality were similar in the two groups. In comparison with the pre‐pandemic period, no AB was recorded during COVID‐19 period, (p = 0.017), while extended‐spectrum beta‐lactamase‐producing EC infections significantly decreased (p = 0.017). Overall, the ESKAPEEc isolates during pandemic less frequently exhibited multidrug‐resistant (p = 0.014). Conclusions These findings suggest that a robust adherence to hygiene measures together with human contact restrictions in a COVID‐19 free ICU might also restrain the transmission of ESKAPEEc pathogens.